The Effect of Performance, Age, Transfer Fee and Salary to the Market Value of Professional Players (Empirical Studies in European Leagues Football Clubs) - Margareta, Lely Marce; Malinda, Okta (iora, 2022)
This study aims to provide empirical evidence about the effect of performance, age, transfer fee, and salary to the market value of professional football players. Data obtained from the official website which publish price of the football players in the transfer market in European leagues that is transfermarkt.co.uk. The population in this study is 4 club in Europe. Based on purposive sampling method, samples obtained as many as 400 players from 40 clubs. The hypothesis in this study tested use multiple regression analysis to test the effect of independent variables on the dependent variable. The research result shows that the performance has positive significant affect the market value of football players, ages has positive significant effect to the market value of football players, incoming transfer fee has positive significant effect to the market value of football players and the salary has positive significant effect to the market value of football players. The conclusion of this study is the performance, age, transfer fee and salary can be used to base appraisals football players in the market value.